Kras oncogene analysis of non-melanoma skin tumors in Southeastern Brazil - Rossit, Andréa [UNESP]; Costa, Fernando; Tajara, Eloiza (My University, 1999)
Skin cancers are the most common human malignant neoplasia and their incidence is growing, chiefly in tropical countries. There is evidence that ultraviolet (UV) radiation present in sunlight is important for genetic damage. Mutations due to such damage could be responsible for alterations in oncogenes and tumor suppressor genes. Recent studies have reported remarkable differences in mutation frequency of the RAS proto-oncogene in non-melanoma skin cancers. These findings may reflect differences in the molecular epidemiology of cutaneous tumors found in geographical areas with diverse sun exposure and ethnical origins of their populations. Our study proposed to perform molecular analyses of skin tumors on patients living in southeastern Brazil, in areas with high levels of sun exposure. DNA from eight solar keratose (SK), 26 basal cell carcinomas (BCC) and 19 squamous cell carcinomas (SCC) was submitted to PCR-SSCP analysis for codons 12, 13 and 61. Contradicting other authors, we found no mutations in codons 12,13 but detected two BCCs and one SCC with a mutation in codon 61. These findings suggest that the activation of KRAS oncogene may contribute to the pathogenicity of cutaneous lesions in southeastern Brazil.
Keywords: Environmental exposure; Radiation exposure; Skin neoplasms; aged; basal cell carcinoma; Brazil; codon; environmental exposure; female; gene activation; gene mutation; genetic analysis; human; human tissue; major clinical study; mutation rate; oncogene k ras; radiation exposure; skin tumor; squamous cell carcinoma; tumor suppressor gene